The Influence of Kpop Idol Brand Ambassador Dimension on Purchasing Decisions Through Purchase intention as an Intervening Variable on Tokopedia - Sylvia Sari Rosalina; Cynthia Veronica Ngantung (Wacana Journal of Social and Humanity Studies, 2022)
The Ambassador brand is one of the marketing strategies that can influence consumer attitudes and beliefs about products. The appointment of the right Brand Ambassador will help increase Brand Awareness. This study aims to determine the influence of the Kpop Idol Ambassador brand dimension on purchasing decisions through purchase intention as an intervening variable on Tokopedia. The population is Indonesians who have used the Tokopedia marketplace for shopping between 2019 and 2021 and know tokopedia's Brand Ambassador advertisements, namely BTS. The sampling technique uses purposive sampling with the criteria of Tokopedia consumers who know tokopedia Brand Ambassador advertisements, namely BTS, as many as 457 respondents. The study's results found that credibility and attraction significantly positively affect purchase intention. On the contrary, power has a positive effect on purchase intention. While credibility and attraction have a positive impact not significantly on purchasing decisions, strength is found to have a significant positive effect on buying decisions. In addition, purchase intention has a significant positive impact on purchasing decisions. In conclusion, credibility and attraction can increase buying decisions if they meet the purchase intention, but power can directly affect buying decisions.